Electrical Discharge Milling with Oblong Tools - Mikesic, Ivan (My University, 2007)
Electrical discharge machining (EDM) is perhaps the most prevalent non-traditional machining process in industry. Therefore, a great amount of effort has been invested towards improving the process. One result of these efforts was the introduction of CNC capabilities to EDM machine tools. Though CNC capabilities are predominantly used for performing orbital EDM, they may also be used for electrical discharge (ED) milling. Cylindrical tools are typically used in ED milling. While other tooling concepts have been developed for use with CNC EDM, this area of EDM is lacking in research. In this work an oblong set of tools for ED milling is presented. The set contains tools capable of machining cavities with both round and sharp features. Motivation for development of the tool set is discussed along with the benefits accompanied by the use of these tools. The cavity profiles considered in this work are divided into three groups based on concavity, continuity and geometric composition. Based on these groups, algorithms are presented for tool type selection and tool size calculation. Tool path planning strategies for each of the tool types are also presented. Two examples are presented in which the algorithms are applied to 2D profiles. The first of these profiles is star shaped, while the second is gear shaped. Both examples were machined on a 4-axis CNC EDM using the oblong tools presented in this work. When compared to equivalent cylindrical/square tools, the oblong tools used for the machining of the cavities provided a substantial increase in frontal area corresponding to improved material removal rates. Furthermore, for both examples, the complete machining of a single layer is accomplished with only one pass of the tool.
Keywords: electrical; discharge; milling; oblong; tool